The adequacy of Sudanese legislation to protect women from gender-based violence - Babeker, AbdulAziz Adam Abdullah (Journal of Economic, Administrative and Legal Sciences, 2017)
Women in many societies are facing unjustified violence. They do not enjoy their full legal rights because of the prevalence of certain harmful habits that establish this kind of violence or because of lack of legislation to regulate the issue. This paper deals with gender based violence, exploring The Sudanese legislations that framed the protection from violence in order to verify the adequacy of these legislations to protect women from this phenomenon. The research problem is focused on the adequacy of protection provided by Sudanese legislation for women to stop the violence against them which based on gender. The researcher used the descriptive approach to study the relevant texts of the Sudanese constitution and laws, to verify the standard of protection provided for women from violence based on gender. This paper concluded to find that, the Sudanese legislation widely framed protection of women from the violence against them. As these legislations covered many aspects of gender based violence; making it suitable to combat this phenomenon if applied in a proper way. But this is success of the Sudanese legislation in its quest to protect women from violence, does not necessarily means the practical application is safe. The discussion here is about the adequacy of the legislation in the single way. In spite of this good frame working to combat gender-based violence; the absence of a specific law to combat this phenomenon in Sudan led to the negligence of some forms of violence against women. In order to strengthen the protection of women from violence, and to complete the legislative shortages in some ways that Sudanese laws did not put a clear cut law about; the paper recommended to enact a special law to combat violence against women. Moreover, Sudanese government and its institutions should educate people of the dangers of harmful habits that contradict the law, religion that represent unjustified violence against women.